Does parental income matter for onset of offending? - Taryn Ann Galloway; Torbjørn Skardhamar (Statistics Norway, Research Department, 2009)
Although several established theories of crime often suggest an association between socio-economic background and youth criminal involvement, the empirical evidence for such claims diverges considerably. The aim of this paper is to re-investigate the relationship between family income and criminal charges by exploiting the rich register data available in Norway. The longitudinal data sources used in the study encompass the entire resident population from five birth cohorts, and allow us to identify youths charged with crimes committed from 1992 to 2004 and link information on these youths with information on family earnings for several years. In a criminal career perspective, our outcome variable is the age of first offence (onset). We find that family academic resources are more important than family income for all kinds of offences, except for serious theft.
Keywords: K14; K40; Z00; 330; SES; parental income; onset of offending; criminal careers